Analisis Derajat Pelapukan Massa Batuan Menggunakan Analisis Petrografi dan Uji Kuat Tekan Uniaksial (UCS) Pada Penambangan Kaolin Daerah Semin, Gunung Kidul, Yogyakarta - Mohammad Suriyaidulman Rianse; Erwin Anshari; Abd. Hadid Rahman Ulfa; Tri Utomo Taliding (OPHIOLITE: Jurnal Geologi Terapan, 2025)
Rock mass weathering is a crucial process that affects the strength and stability of slopes, particularly in mining areas such as Semin, Gunung Kidul. This study aims to analyze the degree of weathering of rock masses in the kaolin mining area using petrographic analysis and uniaxial compressive strength (UCS) testing. Rock samples were collected from three different locations representing varying material conditions based on macroscopic appearance. All the samples are of Altered Mudrock lithology. Sample I is dominated by primary minerals (plagioclase) with a small amount of clay minerals, classified as fresh (grade I). Sample II, which exhibits increased secondary mineral content and porosity, is categorized as slightly weathered (Grade II). Sample III, dominated by secondary minerals (clay and oxides) and with a very low UCS value, is classified as completely weathered (grade V). The results indicate that as the degree of weathering increases, the content of secondary minerals also increases, while the rock strength decreases. Weathering processes, both physical and chemical, alter the mineral composition of rocks, making them more brittle and susceptible to mechanical failure. This study offers valuable insights into how weathering impacts rock stability in mining areas, with implications for safer mine planning and management.